Estimation of the dynamic amplification factor at backfill soil behind a gravity wall. Issue 4 (15th June 2021) - Joseph, Monica; Banerjee, Subhadeep; Pakrashi, Vikram
Abstract : The response of gravity retaining walls under strong earthquake motions is a topic of concern since large catastrophic failures have become more frequent during earthquake and post-earthquake events. Neglecting the amplification of ground motion along the surface was an important reason for severe damages in the 1985 Mexico City earthquake and the 1989 Loma Prieta earthquake. In this paper, the response of a gravity retaining wall under different earthquake motions is analysed using a two-dimensional finite-difference method. The strong-motion parameters, peak ground acceleration (PGA) and predominant frequency are particularly investigated. The responses of the retaining wall in terms of the relative horizontal displacement of the wall, active pressure on the wall and response spectra are analysed for input motions with varying PGA and predominant frequency. An empirical equation for the amplification factor at the top of the wall is developed as a function of the PGA and predominant frequency from the observed results. Such an equation can be particularly helpful for rapid assessments of gravity retaining walls in terms of their earthquake resilience and can be assimilated within the design process with relative ease.